Sequential treatment for idiopathic osteoporosis in premenopausal women: A case report - Mastaglia, Silvina Rosana (2020)
Idiopathic osteoporosis (IOP) affects young, otherwise healthy individuals with intact gonadal function and no secondary cause for bone loss or fragility. IOP may be associated with major osteoporotic fractures such as low-trauma spine or hip. Aim: To evaluate the safety and effectiveness of sequential treatment in premenopausal women diagnosed with IOP. Case Presentation: A33-year-old premenopausal woman was referred by the Gynecology Department to evaluate bone and mineral metabolism.At 28 years of age, the patient had shown a fracture for bone fragility on her right hip. Attaining menarche at age 9, she had regular menstrual cycles (estradiol: 39.3pg/ml and follicle-stimulating hormone: 8.4mIU/l).At the time of consultation, she showed a bone mineral density (BMD, Hologic Equipment, Discovery Wi) in lumbar spine:0.720g/cm2; Z-score: -3.2, and in total left femur: 0.536g/cm2; Z-score: -3.3. No osteoporosis-provoking secondary causes were identified; thus, it was interpreted as IOP. She received sequential therapy (ST) with teriparatide(PTH1-34; Forteo; Eli Lilly&Co., Indianapolis, IN, USA) for two years, and then with densoumab 60mg s.c. (Prolia; Amgen Inc., California, CA, USA) associated with a calcium dietary supply of 1000mg/day and vitamin D3100.000IU/bi-monthly. Results: A 19% increase in LS BMD (least significant change [LSC]: 2.2%) and 16% in FIT (LSC: 3.0%) was observed. Conclusion: The ST was associated with large increase in BMD of LS and FIT in our patient. No adverse effects associated with teriparatide or denosumab were observed. Further clinical studies are necessary to determine the safety and effectiveness of ST in those premenopausal women withIOP. Until then, ST should be used with caution.